3D Imaging of the Environment Mapping and Monitoring - Meneely, John (Taylor & Francis, 2024)
This book gives readers detailed explanations of the techniques used to map and monitor the built and natural environment and how that data, collected from a wide range of scales and cost options, is translated into an image or visual experience. It is written with technical, professional, and academic readers in mind.